Personal Honour and Human Dignity as Fundamental Personal Rights - Kopčová, Radka (Central European Academy Law Review, 2025)
The right to honour and human dignity is a natural subjective right belonging to every natural person and is classified as a personal right. The author comprehensively analyses these two rights under a single construct in the context of the provisions of Section 11 of the Slovak Civil Code. The author also points to other lex specialis of both private and public law regulating the right to honour and human dignity, particularly special provisions on the protection of honour and human dignity of natural persons under criminal law, labour law, and family law. The author exhaustively exposes the common features and fundamental differences between honour and human dignity, using not only legal but also philosophical theories. In connection with the protection of honour and human dignity during life, the author defines the institute of ‘post-mortem protection of human dignity’, the essence of which is to provide protection against unauthorised interferences with these rights after the death of a person. The post-mortem protection of a natural person against unauthorised interferences is categorised at two levels according to the object of legal protection. Comparisons are also conducted between the honour of a natural person and the right to a name and good reputation (‘goodwill’) of a legal person, with the latter regarded as “quasi-personal rights” of legal persons. In this context, she refers to a special legal regulation for the protection of the business name and reputation of an entrepreneur under the law against unfair competition. Then, the author analyses current Czech constitutional case law, according to which legal entities have the right to protect their reputation, similarly to the rights of natural persons.